2007
DOI: 10.1007/s00125-007-0821-y
|View full text |Cite
|
Sign up to set email alerts
|

Increased glomerular cell (podocyte) apoptosis in rats with streptozotocin-induced diabetes mellitus: role in the development of diabetic glomerular disease

Abstract: Aims/hypothesis Podocyte loss by apoptosis, in addition to favouring progression of established diabetic nephropathy, has been recently indicated as an early phenomenon triggering the initiation of glomerular lesions. This study aimed to assess the rate of glomerular cell death and its relationship with renal functional, structural and molecular changes in rats with experimental diabetes. Methods Male Sprague-Dawley rats with streptozotocininduced diabetes and coeval non-diabetic control animals were killed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
64
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 39 publications
5
64
0
Order By: Relevance
“…Although the reason is unclear, one possible explanation is that podocyte apoptosis may be abrogated by the inhibition of the foregoing event, podocyte hypertrophy. Menini et al [45] demonstrated that podocyte apoptosis is not an early feature of experimental DN, as it is preceded by glomerular hypertrophy. In addition, Advani et al [46] found that inhibiting glomerular hypertrophy with an EGF receptor blocker preserves podocyte number in DM glomeruli.…”
Section: Discussionmentioning
confidence: 99%
“…Although the reason is unclear, one possible explanation is that podocyte apoptosis may be abrogated by the inhibition of the foregoing event, podocyte hypertrophy. Menini et al [45] demonstrated that podocyte apoptosis is not an early feature of experimental DN, as it is preceded by glomerular hypertrophy. In addition, Advani et al [46] found that inhibiting glomerular hypertrophy with an EGF receptor blocker preserves podocyte number in DM glomeruli.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro study showed that high glucose-induced apoptosis in podocytes was mediated by p53 pathways (52). In vivo study showed that advanced oxidation protein products induced by diabetes led to podocyte apoptosis by a p53 apoptotic pathway, which was preceded by the increase in albuminuria (53). P53 was upregulated and activated in the renal cortex of db/db mice and streptozotocin (STZ)-induced diabetic mice and rats, leading to the increased podocyte apoptosis and albuminuria (53,54).…”
Section: Sirt1 Inhibits Apoptosis By Targeting P53 Smad7 Foxo3 and mentioning
confidence: 99%
“…In vivo study showed that advanced oxidation protein products induced by diabetes led to podocyte apoptosis by a p53 apoptotic pathway, which was preceded by the increase in albuminuria (53). P53 was upregulated and activated in the renal cortex of db/db mice and streptozotocin (STZ)-induced diabetic mice and rats, leading to the increased podocyte apoptosis and albuminuria (53,54). In addition, p53 could also increase the apoptosis of mesangial cells and tubular cells, resulting in the aggravation of kidney damage (43,54,55).…”
Section: Sirt1 Inhibits Apoptosis By Targeting P53 Smad7 Foxo3 and mentioning
confidence: 99%
See 1 more Smart Citation
“…7) Podocyte loss resulting from apoptosis has played an important role in the onset of albuminuria and the pathogenesis of DN. 8) Recent studies demonstrate that preventing podocyte apoptosis may ameliorate renal injury and decrease proteinuria in DN. 9,10) Recent studies have shown that anti-inflammatory and immunomodulatory actions of minocycline are not related to its antimicrobial property.…”
mentioning
confidence: 99%